1987
DOI: 10.1002/ccd.1810130606
|View full text |Cite
|
Sign up to set email alerts
|

Left main coronary artery embolism: A case report

Abstract: A 27-year-old man had recurrent myocardial infarction found to be due to coronary embolism to the left main coronary artery with downstream embolization. The presumed etiology of thromboembolism was idiopathic cardiomyopathy. A unique method of treatment with Fogarty catheter retrieval was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Maddoux described successful left main coronary artery embolectomy during cardioplegia with transverse aortotomy, using a Fogarty catheter [3]. The failure of balloon angioplasty to establish patency at the site of the embolus may not be surprising in this case.…”
Section: Discussionmentioning
confidence: 81%
“…Maddoux described successful left main coronary artery embolectomy during cardioplegia with transverse aortotomy, using a Fogarty catheter [3]. The failure of balloon angioplasty to establish patency at the site of the embolus may not be surprising in this case.…”
Section: Discussionmentioning
confidence: 81%
“…This argument was further strengthened when an intracardiac thrombus was visualised on the patient's follow-up echocardiography 2 months later. Maddoux et al 6 reported a similar case of LMCA embolus in which the aetiology was unclear but was likely related to cardiomyopathy with mural thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The usual pathophysiological substrate of LMCAT is fibrous cup rupture of an atherosclerotic plaque followed by thrombus formation [2]. However, other predisposing factors include hypercoagulable state, post-partum state, embolization of intracardiac masses, cocaine-induced plaque rupture and vasospasm [2, 5]. …”
Section: Discussionmentioning
confidence: 99%
“…Manual thrombus aspiration in LMCAT has been previously described as a promising therapeutic technique, although data remain sparse [5, 1214]. Maddoux et al were the first to introduce the thrombus aspiration technique as a standalone treatment in a patient with LMCAT complicated with STEMI who followed an uneventful clinical course at 24-month follow-up [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation